Correlation between choroidal structure and smoking in eyes with central serous chorioretinopathy. - Kazuyoshi Okawa; Tatsuya Inoue; Ryo Asaoka; Keiko Azuma; Ryo Obata; Rei Arasaki; Shouko Ikeda; Arisa Ito; Maiko Maruyama-Inoue; Yasuo Yanagi; Kazuaki Kadonosono (PLoS ONE)
Purpose A smoking habit can cause various health problems encompassing retinal diseases including central serous chorioretinopathy (CSC). The aim of the current study was to investigate the effect of smoking on the choroidal structure in patients with CSC. Methods The choroidal vascular index (CVI) was calculated using the binarized OCT images. Baseline parameters (age, refractive error [SE], subfoveal choroidal thickness [SFCT] and CVI) were compared between smokers and non-smokers using Wilcoxon rank sum test. Moreover, the associations between SFCT and the baseline parameters were analyzed using a multivariate linear regression followed by the AICc model selection. Results Among 75 CSC patients, 45 patients were smokers and 30 patients were non-smokers. No significant differences in age and SE were seen between the smoking group and the non-smoking group. A significant difference in the SFCT was seen between two groups (382.0 ± 68.2 μm in the smoking group vs. 339.3 ± 52.3 μm in the non-smoking group, p = 0.0038), while no significant difference was observed in the CVI (p = 0.32). The optimal model for SFCT included the variables of age, SE and past history of smoking among the baseline parameters. Additionally, increased pack years was associated with increased SFCT. Conclusion Cigarette smoking was associated with an increased SFCT in patients with CSC. Thicker choroid in smoking CSC patients may be an important modulator of the disease.